AN ANALYSIS OF COMMISSIVE SPEECH ACTS USED BY THE MAIN CHARACTERS IN WOMEN-CENTRIC MOVIES - Ashfiya, Hamadah; Degaf, Agwin (International Journal of Humanity Studies (IJHS), 2023)
This study explores the usage of commissive speech acts in the women-centric movies "Little Women" and "Enola Holmes." It employs Searle's classification of speech acts (1979), along with Hymes' social structure theory (2001) and Brown Levinson's politeness theory (1987). The analysis uncovers various types of commissive speech acts in movies set in the nineteenth century. Furthermore, it reveals that the employment of commissive speech acts and the politeness strategies employed by the characters are significantly influenced by the social structure of their respective societies. These findings contribute novel insights to the existing theories and extend the scope of sociopragmatics research, particularly in evaluating movies within academic settings. The study suggests conducting further research encompassing diverse cases, exploring other aspects of speech act studies, and engaging in comparative or cross-cultural analyses.